1993
DOI: 10.1093/infdis/168.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endotoxin Release by Different Antimicrobial Agents and the Effect on Inflammation in Experimental Escherichia coli Meningitis

Abstract: In a rabbit Escherichia coli meningitis model, endotoxin liberation and concentrations of leukocytes, tumor necrosis factor (TNF), and lactate were compared after a single intravenous dose of cefotaxime, cefpirome, meropenem, chloramphenicol, or gentamicin. These antibiotics caused a 2- to 10-fold increase in cerebrospinal fluid concentrations of free (filterable) endotoxin within 2 h of starting treatment. By contrast, free endotoxin concentrations increased almost 100-fold in untreated animals 4 h later as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
4
31
0
1
Order By: Relevance
“…Some studies show even a transitory worsening of the inflammation after antibiotic administration, possibly due to the enhancement of endotoxin release (153,324). This finding contrasts with studies of sepsis, where antibiotic-induced endotoxin release has never been observed (see "Pathophysiology of shock," above, and "Antibiotic treatment" below).…”
Section: Pathophysiology Of Meningococcal Meningitismentioning
confidence: 93%
See 1 more Smart Citation
“…Some studies show even a transitory worsening of the inflammation after antibiotic administration, possibly due to the enhancement of endotoxin release (153,324). This finding contrasts with studies of sepsis, where antibiotic-induced endotoxin release has never been observed (see "Pathophysiology of shock," above, and "Antibiotic treatment" below).…”
Section: Pathophysiology Of Meningococcal Meningitismentioning
confidence: 93%
“…Some investigators have suggested that antibiotics exacerbate meningeal inflammation by stimulating endotoxin release (11,324), and have therefore suggested postponing antibiotic treatment until after dexamethasone was given (405). However, these recommendations are dangerous, since proliferating bacteria shed more endotoxin than those exposed to antibiotics and delay in sterilization of CSF worsens the prognosis (153,273).…”
Section: Treatment Of Meningitismentioning
confidence: 99%
“…In general, such studies showed a decrease in bacterial counts concurrent with an increase in endotoxin levels in antibiotic-treated animals or a larger increase in endotoxin levels in treated than in untreated animals. This was demonstrated in experimental E. coli sepsis in rabbits (65,69) and pigs (63), H. influenzae sepsis in rats (79), meningococcal sepsis in mice (20), and E. coli (35,73) Parallel with a higher increase in endotoxin levels in antibiotic-treated animals, some studies reported higher TNF levels (35,54,57), but a correlation between a rise in endotoxin level and interleukin 6 levels could not be demonstrated (23). Although corticosteroids appear to have no influence on the process of antibiotic-induced endotoxin release (31,57), the TNF response of the host could be attenuated by dexamethasone (54,57).…”
Section: Studies In Animalsmentioning
confidence: 99%
“…The release of bacterial cell wall fragments giving rise to the brain production of IL-1, IL-6, and TNF-␣ will not only exacerbate inflammation, but also further damage the blood-brain barrier (4 -7). However, in recent studies of experimental Escherichia coli meningitis, the amount of bacterial endotoxin ultimately released as a consequence of bacteriolysis was much lower than that released by bacteria not being exposed to antibiotics (8). This finding led us to hypothesize whether there might be another virulence factor for exacerbating inflammation as a consequence of antibiotic treatment.…”
mentioning
confidence: 96%